Phosphorus Contents Re-visited After 40 Years in Muddy and Sandy Sediments of a Temperate Lagoon System - Berthold, Maximilian; Zimmer, Dana; Reiff, Volker; Schumann, Rhena (Frontiers in Marine Science, 2018)
Worldwide, coastal water bodies suffer from anthropogenically elevated nutrient inputs, which led to eutrophication. Sediments in eutrophic systems are assumed to be an important internal nutrient source. The total phosphorus (TP) concentration (mg g-1 dry mass) is widely used as a proxy for the sediment nutrient load. 2-D distribution maps of TP concentrations are used for management plans, where areas of high TP values are marked in red. However, the sediment density is lowered at increasing water content, which can lead to different TP stocks per g m-2. The aim of this study was, to do a re-evaluation of TP concentrations and stocks in the model ecosystem of the Darß-Zingst Bodden chain, a typical lagoon system of the southern Baltic Sea. Sediment cores were taken at eight stations along transects from shallow to deeper parts of the lagoon. Samples were analyzed for TP, water and organic content, as well as density. This data set was compared to results from a sediment survey during the time of highest nutrient inputs (40 years ago) at the same sampling stations. TP concentrations from 40 years ago and today were in the same range. The highest TP concentrations (up to 0.6 mg TP g-1 dry mass) were found in the deeper basins and lowest concentrations in the shallow areas of the lagoon (down to 0.05 mg TP g-1 dry mass). However, normalization over dry bulk density reversed some results. The highest TP stocks (up to 5 g TP m-2) were then found in the shallow areas and lowest stocks (down to 0.2 g TP m-2) in the deeper parts of the lagoon. Some stations did not exhibit any differences of TP at all, even after including the dry bulk density. These findings suggest that there seems to be no up-, or downward trend in nutrient concentrations of sediments even after 25 years of reduced external nutrient inputs. Furthermore, TP stocks point to possible diffuse P entry pathways that counteract external nutrient reductions. These findings can have an impact on possible countermeasures for ecosystems rehabilitation, like sediment removal or nutrient reductions in the adjacent land.